Spiritual Capital, Human Capital, and Knowledge Management in Indonesian Hajj Service Quality: A Maqāṣid and Fiqh al-Khidmah Systematic Review - Suhendra Suhendra; Sudarnoto Abdul Hakim; Lukman Lukman; Mohammad Taqiuddin bin Mohamad (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2026)
The quality of Hajj services in Indonesia is conventionally analysed through managerial frameworks that treat officer competence as an administrative rather than a juridical variable. This study challenges that framing by situating spiritual capital, human capital, and knowledge management within the normative architecture of fiqh al-khidmah and maqāṣid al-sharīʿah, and by determining the ḥukm taklīfī governing spiritual capital in the specific context of khidmah al-ḥujjāj. A Systematic Literature Review (SLR) structured according to the PRISMA protocol synthesises 48 Scopus-indexed studies published between 2020 and 2025. The PRISMA workflow governs source identification and selection, while an istinbāṭ-oriented analytical layer derived from uṣūl al-fiqh governs normative interpretation, applying the maqāṣid hierarchy (ḍarūriyyāt, ḥājiyyāt, taḥsīniyyāt), selected qawāʿid fiqhiyyah — principally al-masyaqqah tajlib al-taysīr, taṣarruf al-imām ʿalā al-raʿiyyah manūṭ bi al-maṣlaḥah, and al-wasāʼil lahā ḥukm al-maqāṣid — and the principle of sadd al-dharāʼ iʿ as interpretive instruments. The synthesis finds that human capital is a necessary but insufficient determinant of service quality; spiritual capital, grounded in taqwā, amānah, and iḥsān, functions as a sharʿī-normative asset whose ʿillah is not private piety but the realisation of ḥifẓ al-dīn and ḥifẓ al-nafs for the pilgrim; and knowledge management constitutes the organisational wasīlah that operationalises both capitals in accordance with maqāṣid objectives. The resulting ḥukm taklīfī positions spiritual capital as ḥājī rising to ḍarūrī whenever its absence foreseeably endangers the pilgrim’s religious or physical integrity, and identifies knowledge management as a sharʿī wasīlah whose neglect is juristically censured wherever it produces loss of maṣlaḥah to the pilgrim. These findings are synthesised into a “Sharīʿah-Informed Service Profit Chain” model that reframes officer performance as a taklīf sharʿī rather than an administrative duty, contributing to fiqh al-khidmah a normative framework applicable to state-administered religious services beyond the Hajj context